نمطا الانفوجرافيك (الثابت - الديناميكي) بمقرر إلكتروني ببيئة التعلم الإلكتروني "الموودل" وأثرهما على تنمية التحصيل والتفكير الناقد لدى طلاب تكنولوجيا التعليم - بيومي، إيمان عطيفي (الجمعية المصرية لتكنولوجيا التعليم, 2020)
يعد الإنفوجرافيك تكنولوجيا جديدة للتعليم، فهو يمنح المتعلم مجموعة من المعلومات والبيانات وبالنهاية نتيجة وملخص لهذه المعلومات مما يسهل قراءتها ويحقق هدفها في إيصال الرسالة الصحيحة للمتعلم، فهذا النوع من التصميم لا يعد فقط مجرد أرقام أو رسوم بيانية أو تصاميم وإنما هو مواد ودراسات بحثية معقدة تم تبسيطها وتحليلها وإخراجها برسم بياني لتسهل على المتعلم استقبال الرسالة البصرية. بالإضافة إلى خلق بيئة تعلم جديدة ومواقف تعليمية جديدة تقوم على أساس المعالجة والتفاعل. ومع ذلك فهو غير موظف بشكل جيد في التعليم، ويحتاج إلى زيادة فاعليته وكفاءته، وذلك عن طريق دراسة متغيرات عديدة خاصة بالإنفوجرافيك. وتعد أنماط الإنفوجرافيك في بيئة التعلم الإلكتروني "الموودل" من أهم المتغيرات، لأنها هي الأساس في زيادة فاعليته وكفاءته، وزيادة تفاعل المتعلم معه. ومن هنا وجدت الحاجة إلى دراسة نمطا الإنفوجرافيك (الثابت- الديناميكي) بمقرر إلكتروني ببيئة التعلم الإلكتروني "الموودل"" وأثرهما على تنمية التحصيل والتفكير الناقد لدى طلاب تكنولوجيا التعليم. وبالرغم من وجود دراسات قدمت مقارنات بين الإنفوجرافيك الثابت والمتحرك إلا أنها كانت معالجات جزئية، ولا توجد بحوث عديدة حول متغيرات نمطا الإنفوجرافيك الثابت والديناميكي، لذلك يهدف البحث الحالي إلى دراسة نمطا الإنفوجرافيك (الثابت- الديناميكي) بمقرر إلكتروني ببيئة التعلم الإلكتروني "الموودل"" وأثرهما على تنمية التحصيل والتفكير الناقد لدى طلاب تكنولوجيا التعليم. ولتحقيق هذا الهدف تم دراسة نمطا الإنفوجرافيك (الثابت- الديناميكي) بمقرر إلكتروني فهناك النمط الثابت وهو الأكثر انتشارا من بين أنماط الإنفوجرافيك ويستخدم في تمثيل البيانات الغنية في صورة واحدة، ويتميز بالسهولة النسبية في إعداده، ويستخدم في تقديم المعلومات التي لا تحتاج إلى تحديث، ونمط الإنفوجرافيك الديناميكي حيث يتم توليد معلومات جديدة بالإضافة إلى التغيير من شكله والتحكم في عرضه من خلال بيئة التعلم الإلكتروني "الموودل""، ثم إتباع منهج البحث التطويري لتطوير نمطا الإنفوجرافيك (الثابت- الديناميكي) بمقرر إلكتروني ببيئة التعلم الإلكتروني "الموودل"" وأثرهما على تنمية التحصيل والتفكير الناقد لدى طلاب تكنولوجيا التعليم. وأعدت أدوات البحث التي تمثلت في معايير تصميم الإنفوجرافيك عرضه من خلال بيئة التعلم الإلكتروني "الموودل"، والاختبار المعرفى لطلاب الفرقة الثالثة شعبة تكنولوجيا التعليم لمادة الإحصاء التطبيقي والحاسب الآلي، واختبار تفكير ناقد نحو نمطا الإنفوجرافيك (الثابت- الديناميكي) بمقرر إلكتروني ببيئة التعلم الإلكتروني "الموودل" لطلاب الفرقة الثالثة شعبة تكنولوجيا التعليم لمادة الإحصاء التطبيقي والحاسب الآلي، وطبقتها على عينة من ١٤٠ طالبا وطالبة.
Infographics is a new technology for education, it gives the learner a set of information and ultimately the result and summary of this information that makes reading and achieving its goal in any message the correct message for the learner, this type of design is not only just numbers or graphs or designs used is a complex research materials and studies have been Simplify, analyze and output it with a graph to make it easier for the learner to receive the visual message. And also to create a new learning environment and new educational situations based on treatment and interaction. However, it is not well employed in education, and it needs to increase its effectiveness and efficiency, by studying several variables related to infographics. Hence, I found the need to study the infographic pattern (static - dynamic) with an electronic course in the e-learning environment and their impact on the development of achievement and critical thinking among students of educational technology. Although there are studies that have provided comparisons between fixed and mobile infographics, they were partial treatments, and there are not many researches on variables of the fixed and dynamic infographic pattern, therefore the current research into the study of infographic (static - dynamic) pattern with an electronic course in the e-learning environment and their impact on the development of achievement and critical thinking Among students of educational technology. To achieve this goal, the infographic pattern (static - dynamic) was studied by an electronic course. There is the fixed pattern, which is the most prevalent among the infographics patterns and is used to represent rich data in one image, and is characterized by the relative ease in its preparation, and is used in providing information that does not need updating, and a pattern Dynamic infographics as new information is generated in addition to changing its shape and controlling its presentation through the e-learning environment, then following the developmental research method to develop the infographic (static - dynamic) pattern with an electronic course in the e-learning environment and their impact on The development of achievement and critical thinking technology education students The research tools that were represented in the standards of infographic design were prepared to display it through the e-learning environment, the cognitive test for students of the third year, the Division of Education Technology for Applied Statistics and the Computer, and the test of critical thinking towards the pattern of infographic (static - dynamic) with an electronic course in the e-learning environment for the third year division students Teaching technology for applied statistics and computer, and applied it to a sample of 140 students.
Keywords: التعليم الإلكتروني -- المقررات الإلكترونية -- بيئة التعلم الإلكترونية -- برنامج مودل -- الانفوجرافيك -- التحصيل الدراسي -- التفكير الناقد -- طلبة تكنولوجيا التعليم -- جامعة الفيوم